PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN PAJAK - Maria Meilinda; Nur Cahyonowati (Diponegoro Journal of Accounting, 2013)
This research investigates the influence of corporate governance influences on  tax management  behavior.  Tax management is measured by effective tax rate. Corporate governance are measured by number of commissioner, percentage of independent commissioner, and compensation of commissioner and executives. Company size, profitability, debt ratio, and different tax rate are used as control variables.This  research  sample  is manufactured company selected by  using  method  of purposive  sampling.  There  are  153  companies  fulfilling  criterions. This research used multiple regression analysis. The  results  of  this  research  indicates  that  the number of commissioner, company size, profitability, and debt ratio affect tax management significantly. Meanwhile, the proportion of independent commissioners, compensation of commissioner and executive, and  different tax rate does not significantly influence the company's tax management.